Attitudes Toward Telehealth Services Among People Living With Parkinson's Disease: A Survey Study. Issue 6 (26th March 2022) - Xu, Yaqian; Feeney, Megan P.; Surface, Matthew; Novak, Dan; Troche, Michelle S.; Beck, James C.; Alcalay, Roy N.
ABSTRACT: Background: Telehealth has been widely adopted in providing Parkinson's disease care during the coronavirus disease 2019 pandemic. Objective: The aim of this study was to survey people living with Parkinson's disease (PwPD) about their attitudes toward and utilization of telehealth services. Methods: A survey was administered to PwPD via Parkinson's Foundation and Columbia University mailing lists. Results: Of 1, 163 responses, 944 complete responses were analyzed. Telehealth awareness was 90.2% (850/942), and utilization was 82.8% (780/942). More than 40% of PwPD were equally or more satisfied with telehealth compared with in‐person visits in all types of services used. The highest satisfaction was observed in speech‐language pathology appointments (78.8%, 52/66) followed by mental health services (69.2%, 95/137). Conclusions: In selected circumstances and indications, such as speech‐language pathology and mental health services, telehealth may be a useful tool in the care of PwPD beyond the coronavirus disease 2019 pandemic. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.